Security Education for Smart Grid: Materials, Experiments, and Evaluation (Journal of The Colloquium for Information Systems Security Education, 2015)
With the fast development of Cyber-Physical Systems (CPS), security in these special application environments starts to attract more and more efforts. In this project, we form a team of researchers in information security, power systems, simulation, and education evaluation to jointly develop educational materials and experiments for security education in smart grid. Multiple course modules for infrastructure and data security in smart gird have been designed. We design a simulation/emulation based experiment platform and develop several student projects upon it. These materials have been adopted by both graduate and undergraduate level security courses. Formal evaluations are conducted by third party evaluators.